The Role of Company Size Moderation in the Determinants of Dividend Policy (Study of Financial Sector Companies Listed on the Indonesia Stock Exchange in 2019-2022) - Hidayah, Nurul; Sukesti, Fatmasari S (Economics and Business International Conference Proceeding, 2024)
The purpose of this study is to determine precisely the influence of leverage, profitability and liquidity on dividend policy, as well as to determine the influence of company size in moderating or strengthening the independent variables of the research, namely leverage, profitability and liquidity on the dependent variable, namely dividend policy. The type of research used in this study is quantitative which has a population of all financial sector companies listed on the Indonesia Stock Exchange (IDX) in 2019-2022. The data collection technique in this study is purposive sampling. In this study, a sample of 22 financial sector companies listed on the Indonesia Stock Exchange in 2019-2022 was studied. The technique used in analyzing research data is Moderated Regression Analysis (MRA) with Micosoft Excel Application and SPSS Version 26 for research data processing. Based on the results of the research hypothesis testing that has been carried out, it shows that Profitability has a positive effect on dividend policy, while Leverage and Liquidity have no effect on dividend policy. As well as the variable size of the Company can moderate the relationship between Profitability and dividend policy while the Company Size is not able to moderate the relationship between Leverage to dividend policy and Liquidity to dividend policy.